Charcoal characterization and application is solar evaporator for seawater desalination - J., Roslan; W., Eh Kan; A. K., Abdul Rahman; M., Suliman; R., Isha (IOP Publishing, 2020)
Solar desalination is the most attractive and simple technique for desalination process but suffers low thermal efficiency. The objective of this research is to study the effect of charcoal in seawater desalination for clean water production. The experiment was conducted in a basin type solar evaporator by using seawater with charcoal to seawater mass ratio variation of 1:50 to 1:500. The investigation was carried out for eight hours in sunny daylight. The water qualities including pH, conductivity, total dissolve solid (TDS), chemical oxygen demand (COD) and turbidity of the seawater and amount of evaporated water were determined. The spent and fresh charcoals were also characterized by using Nitrogen Adsorption (BET), X Ray Detector (XRD) and Scanning Electromagnetic Microscope (SEM). It is found that the addition of charcoal in the water leads to20 % increment of water temperature. Charcoal’s exposed area to the energy source significantly affects the temperature raise. The best charcoal to water mass ratio was achieved at 1:100 to produce 16.8% evaporated water. Charcoal was stable in seawater because minimum changes of pore size and pore volume were observed. In conclusion, charcoal is a potential salt adsorbent and medium for solar thermal energy storage for seawater solar desalination process.